Legal Compliance with the Implementation of Religious Holiday Allowance in the Healthcare Industry of Samarinda City - Marwah M Idris; Rio Arif Pratama; Asnawi Mubarok (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The implementation of the Religious Holiday Allowance (Tunjangan Hari Raya; THR) remains a critical issue in Indonesian labour law because employer non-compliance may undermine the protection of employees’ normative rights. This study aimed to analyse employers’ legal compliance with THR regulations in the healthcare industry in Samarinda City, classify the characteristics of such compliance according to Herbert C. Kelman’s theory of legal compliance, and examine its implications for employee rights protection. An empirical legal approach with a qualitative design was employed. Data were collected through interviews, observations, and document analysis involving hospitals, clinics, and pharmacies and were examined using qualitative descriptive analysis. The findings indicate that THR implementation generally complied with applicable legal provisions concerning payment mechanisms, employee eligibility, allowance amounts, wage components, and payment deadlines. Nevertheless, several forms of non-compliance were identified, including delayed payments, improper calculation or provision of THR for employees with less than one year of service, and the failure of certain employers to provide THR to eligible employees. Based on Kelman’s framework, most employers demonstrated compliance motivated by adherence to legal requirements, only a limited number had reached the internalization stage, and several remained non-compliant. The study concludes that the degree and motivation of employers’ legal compliance directly shape the effectiveness of legal protection for employees’ normative rights. These findings contribute to labour law enforcement scholarship by demonstrating that formal compliance alone is insufficient to ensure sustainable employee protection. Strengthening employers’ legal awareness, regulatory supervision, and consistent law enforcement is therefore necessary to ensure the equitable and sustainable implementation of THR in the healthcare industry.